Pendidikan Islam Humanis Sebagai Solusi Kekerasan Dalam Pendidikan - Moh. Eko Nasrulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
Violence is the center of attention in education circles. The emergence of violent events in education in Indonesia in this global era makes education scholars trying hard to find a solution to solve the problem. The digital era is full of technological advances also allows changes in society to the moral values adopted. Although the reality of violence can not be eliminated 100% 100% in education, but educational practitioners should make maximum effort to realize a humanist education in school. By evaluating the events that occur then sought the right solution in order to be able to change the conditions. A case can not find a solution directly without analyzing what factors affect the occurrence of events. By doing the study from another scientific point of view is expected to be able to understand the facts in depth. Considering factors affecting social interaction such as imitation, suggestion, identification, and sympathy can be used in understanding the details of the problem. The effort to study the nature of Islamic human education becomes an important part in finding solutions. The cultivation of human values needs to be done in the learning process. an educator must have competence Procedures handling students who interfere with the learning process and juvenile delinquency. Mild intervention, moderate intervention, and greater intervention can be used as an option by an educator in dealing with student behavioral disorders in the learning process.Keywords: Islamic humanist education, education violence,